Agrobacterium-mediated Transformation of Banana Musa acuminata AA cv "“Mas Lampung” with hpt Gene Using Sterile Corm as Target Tissue - Estiati, Amy; Nena, Ade; Witjaksono, Witjaksono (Annales Bogorienses, 2009)
The protocol for Agrobacterium-mediated transformation of local banana plants cv “Mas Lampung” (AA) has been established. A selectable marker gene (hpt) has been used to study the transformation using in vitro corm slices as target tissues. Banana in vitro corm slices were co-cultivated with the EHA105 strain of Agrobacterium tumefaciens harbouring binary vector pCAMBIA 1301 containing hygromycin resistance gene (hpt) as a selectable marker and intron-containing β-Glucuronidase (gus-intron) gene as a reporter gene driven by CaMV 35S promoter. Polymerase Chain Reaction (PCR) were used to examine the existence of hpt gene in plants resulted from the transformation. Using primer pairs specific for hpt gene, our PCR analysis on leaves showed the presence of the hpt transgene in banana transgenic plants at first generation (T0) of transformation. To prove the existence of hpt gene in the fruits of transgenic banana plants, PCR analysis were also carried out. The data showed that the hpt gene could be amplified from banana fruits of tested samples. These result demonstrates that the Agrobacterium-mediated transformation method used in this experiment has been successful to transfer gene into banana plants. Thus, the transformation method reported here could be used as a standard protocol to transfer another useful genes into local banana plants cv. “Mas Lampung”. Furthermore, the presence of transgene in fruits of banana transgenic plants is important achievement especially for transgene that is expected to be expressed in the fruit including to introduce vaccine genes into banana fruits for edible vaccine.